(NkWANTOWOMEHANI^ESKAQ TEORIQ WOZMU]ENIJ (B((NDIAGRAMMNYJ METOD(B) :s (Nu^EBNOE POSOBIE (B/s - (NkISELEW(B, (NaLEKSEJ aLEKSEEWI^s; (NlQPCEW(B, (NaLEKSANDR wIKTOROWI^s; (NdMITRIEW(B, (N`(B.(N`(B.s ((Nl(B. :s (Nlgu(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 355-358 (92 (NNAZW(B.)s
Keywords: (NwOZMU]ENIJ TEORIQs